Prevalence of Clostridium Difficile Infection (CDI) among Inflammatory Bowel Disease (IBD) Patients in Comparison to Non-IBD Patients in King Abdulaziz Medical City in Jeddah - Ghassan Abdulrahman Sukkar; Syed Sameer Aga; Abdulrahman Hamid Alsamadani; Faisal Ghazi Almalki; Ali Saleh Alsudais; Abdulrahman Sulaiman Alquzi; Mohamed Eldigire Ahmed; Mushtaq Ahmad Mir; Moudi M. Alasmari (Interdisciplinary Perspectives on Infectious Diseases)
Background. The prevalence of Clostridium difficile infection (CDI) as a common complication among inflammatory bowel disease (IBD) has been reported to increase worldwide and has been associated with a poor IBD outcome. Objectives. In this study, our aim was to report on the prevalence of CDI among IBD vs. non-IBD patients in King Abdulaziz Medical City (KAMC). Methods. This retrospective descriptive study was carried out between 2016 and 2020. Data of 89 patients reported with CDI in KAMC were analyzed for demographics and correlations between various characteristics such as BMI, personal/family history of IBD, infection with CDI, diagnosis, method of diagnosis, and treatment modalities. Results. Of the total 89 CDI patients, 59 (66.3%) were adults and 30 (33.7%) were pediatric, of which 36 (40.4%) were females and 53 (59.6%) were males. PCR was the main method of choice for the diagnosis of CDI (89.9%) followed by a positive-culture result (10.0%). Seventy-eight (87.6%) CDI patients were found to be immunocompromised, with two patients diagnosed with IBDs, one with UC, and one with CD. The recurrence rate was 38.4 (30 patients) among the immunocompromised group in comparison to 27.2 (3 patients) in the immunocompetent group (p=0.584). Conclusion. In this study, we found that adults were more prone to CDI infection, especially within hospital settings, and most of the CDI infections occurred in immunocompromised individuals, with cancer as the most common cause of it.